2023
DOI: 10.1186/s13041-022-00986-9
|View full text |Cite
|
Sign up to set email alerts
|

Knee osteoarthritis accelerates amyloid beta deposition and neurodegeneration in a mouse model of Alzheimer’s disease

Abstract: Knee osteoarthritis (OA) is characterized by knee cartilage degeneration and secondary bone hyperplasia, resulting in pain, stiffness, and gait disturbance. The relationship between knee OA and neurodegenerative diseases is still unclear. This study used an Alzheimer’s disease (AD) mouse model to observe whether osteoarthritis accelerates dementia progression by analyzing brain histology and neuroinflammation. Knee OA was induced by destabilizing the medial meniscus (DMM) in control (WT) and AD (5xFAD) mice be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Previous studies (Innes & Sambamoorthi, 2018; Lin et al, 2022) showed that patients with KOA have impaired cognitive function, mainly in memory disturbances which are partly consistent with our results. Gupta et al (Gupta et al, 2023) found that OA was a risk factor for Alzheimer's disease (AD)…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Innes & Sambamoorthi, 2018; Lin et al, 2022) showed that patients with KOA have impaired cognitive function, mainly in memory disturbances which are partly consistent with our results. Gupta et al (Gupta et al, 2023) found that OA was a risk factor for Alzheimer's disease (AD)…”
Section: Discussionmentioning
confidence: 99%
“…In a lead study conducted by Gupta et al [ 102 ] to analyze the association between knee OA and AD on 5xFAD transgenic mice models, induction of OA in the AD mice led to a more exacerbated symptom in certain brain regions, increased inflammation including elevated IL-1β and TNF levels, and more Aβ disposition. This study helps us understand how OA development can exacerbate pathologies related to AD development.…”
Section: Ad Development and Oa: An Extensive Insightmentioning
confidence: 99%
“…During these chronic pain states, microglia release pro-inflammatory cytokines, including IL-6, IL-1β, and TNF-α, which cause dysfunction in synaptic remodeling and brain connectivity [ 100 , 113 , 116 ]. In addition, it has been reported to increase the mRNA expression of IL-1β and TNF-α and accelerate Aβ deposition in 5xFAD model mice [ 117 ]. Chronic pain-induced microglial inflammation is associated with AD progression.…”
Section: Pain Is a Risk Factor For Ad: Possible Involvement Of Microg...mentioning
confidence: 99%